Pengaruh Tingkat Suku Bunga dan Nilai Tukar Terhadap Return Saham dengan Profitabilitas Sebagai Variabel Intervening pada Perusahaan Perbankan yang Terdaftar di BEI Periode 2020–2024 - Irawan, Fajar Rayhan Putra; Yenni, Zefri; Yeni, Fitri (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyse the effect of interest rates and exchange rates on stock returns with profitability as an intervening variable in banking companies listed on the Indonesia Stock Exchange for the period 2020–2024. This study uses a quantitative approach with an explanatory research type. The research population includes all banking companies listed on the IDX, with purposive sampling techniques resulting in a sample of 27 companies. The data used is secondary data obtained from annual financial reports and related official publications. The data analysis method used path analysis with the help of statistical software to test the direct and indirect effects between variables. The results showed that interest rates did not have a significant effect on profitability, while exchange rates had a significant effect on profitability. Interest rates and exchange rates did not have a significant direct effect on stock returns. Profitability was found to have a significant effect on stock returns. Furthermore, interest rates have a significant effect on stock returns through profitability as an intervening variable, while exchange rates do not show a significant indirect effect through profitability. These findings indicate that profitability plays an important role in bridging the influence of macroeconomic factors on banking stock returns.